EFFECTS OF PROGRAM OF INTENSIVE TRAINING OF ALPINE SKIING TECHNIQUES ON SOME MORPHOLOGICAL CHARACTERISTICS - Mijo Ćurić,; Edin Mujanović,; Amra Nožinović-Mujanović,; Almir Atiković,; Jasmin Mehinović,; Nermin Nurković, (Sport Scientific And Practical Aspects, 2025)
The aim of this research was to determine the effects of experimental short-term program of intensive training of alpine skiing techniques (experimental program) on morphological characteristics (body composition) of students. The sample is divided into an experimental group (31 males, age 21.4 ± 1 and body height 180.7 ± 6.3cm) beginners who were on skis for the first time and control group (34 males, age 20.6 ± .8 and body height 180.3 ± 6.8 cm). The following body parameters were measured at the beginning and end of the experimental program: body weight, body mass index, fat percent, total weight (in kg) of fat in the body, total weight (in kg) of body mass without body fat, total weight (in kg) of water in the body. To determine the effects of an experimental program on some morphological characteristics of students a univariate covariance analysis was applied. Results of ANCOVA show statistically significant effects of the applied experimental program in variable total weight (in kg) of water in the body p = .018 where the variable showed higher values for the experimental group compared to the control group.